Effect of fatigue induced by YoSFS⁵ after FIFA 11+ injury prevention program on anterior cruciate ligament injury risk among youth male recreational soccer players / Saiful Adli Bukry - Bukry, Saiful Adli (2022)
Injury among youth soccer players is increasing as more youth population participates in this sport. Thus, injury prevention program such as FIFA 11+ is crucial to reduce the rate of injury. However, FIFA 11+ has not been tested for effect on the youth population during fatigue state. Therefore, this study aimed to investigate the effect of eight weeks of FIFA 11+ injury prevention program on isokinetic strength, dynamic balance and biomechanics during landing following fatigue induction among youth soccer players. This study was divided into two phases. In the first phase, there are two objectives have been investigated. Firstly, was to determine the reliability and validity of a newly developed high-intensity Youth Soccer Fatigue Simulation (YoSFS5 ). Twenty recreational male youth soccer players (age:15.9±0.87, years old, BMI =19.52±2.58 kg/m2 ) performed the YoSFS5 in 5 minutes after performing a dynamic warming-up. Heart rate (HR), rate of perceived exertion (RPE), and countermovement jump (CMJ) height were recorded immediately after completing the YoSFS5 . After a week, the participants repeated the same procedure and measurements. Secondly, this study was to investigate the effect of YoSFS5 on the isokinetic strength, dynamic balance and biomechanics during landing of the lower limbs in youth soccer players. Thirty-nine youth soccer players performed tests on isokinetic strength, dynamic balance, and biomechanics during landing before the fatigue simulation (PRE), immediately after simulation (POST5), and 20-min (POST20), and 35-min (POST35). Lastly, to investigate the effect of 8 weeks FIFA 11+ injury prevention program on isokinetic strength, dynamic balance, and biomechanics during landing following YoSFS5 among youth soccer players. Thirty participants were volunteers and randomly allocated into two groups (FIFA11+ vs control). The participants followed the same procedures in objective two, then went to intervention 2 times/week for 8 weeks long. After that, all participants have repeated the same procedure before the intervention. The result of the first objective has shown that the relative and absolute reliability was considered between good to excellent (ICC = 0.72-0.92). The absolute reliability showed a small percentage of CVs for HR, RPE, and CMJ at 0.9%, 5.5%, and 8.35%, respectively.